2015
DOI: 10.1016/j.jmbbm.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion profile of macromolecules within and between human skin layers for (trans)dermal drug delivery

Abstract: Diffusion profile of macromolecules within and between human skin layers for (trans)dermal drug delivery, Journal of the Mechanical Behavior of Biomedical Materials, http://dx.doi. org/10.1016/j.jmbbm.2015.06.019 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Even with such methods however, the relatively low diffusivity of high molecular weight compounds can impede delivery. [305] The combination of various modalities of enhancing flux may be beneficial. For example, the combination of micron-scale disruption (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Even with such methods however, the relatively low diffusivity of high molecular weight compounds can impede delivery. [305] The combination of various modalities of enhancing flux may be beneficial. For example, the combination of micron-scale disruption (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Injections are more expensive and require professional training for administration (Wu et al, 2016;Arya et al, 2017). Transdermal drug delivery is an attractive alternative to oral administration or injection, and early studies confirmed that it could overcome the above-mentioned problems (Prausnitz & Langer, 2008;Romgens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their size, macromolecules can also diffuse across membranes, as shown, for example, across skin layers [114]. Their delivery can also be achieved with an external stimulus.…”
Section: Macromoleculesmentioning
confidence: 99%